Cocaine From Coca Fields to the Streets - Arias, Enrique Desmond; Grisaffi, Thomas (Duke University Press, 2021)
The contributors to Cocaine analyze the contemporary production, transit, and consumption of cocaine throughout the Americas and the illicit economy's entanglement with local communities. Based on in-depth interviews and archival research, these essays examine how government agents, acting both within and outside the law, and criminal actors seek to manage the flow of illicit drugs to both maintain order and earn profits. Whether discussing the moral economy of coca cultivation in Bolivia, criminal organizations and drug traffickers in Mexico, or the routes cocaine takes as it travels into and through Guatemala, the contributors demonstrate how entire ways of life are built around cocaine commodification. They consider how the authority of state actors is coupled with the self-regulating practices of drug producers, traffickers, and dealers, complicating notions of governance and of the relationships between economic and moral economies. The collection also outlines a more progressive drug policy that acknowledges the important role drugs play in the lives of those at the urban and rural margins.Contributors. Enrique Desmond Arias, Lilian Bobea, Philippe Bourgois, Anthony W. Fontes, Robert Gay, Paul Gootenberg, Romain Le Cour Grandmaison, Thomas Grisaffi, Laurie Kain Hart, Annette Idler, George Karandinos, Fernando Montero, Dennis Rodgers, Taniele Rui, Cyrus Veeser, Autumn Zellers-León